Letter : Confidential - Azcárate, Pablo de, 1890-1971
034-0130-001 EMBAJADA DE ESPAÑA London, October 7th., 1938. Your ref: Secretary's Department. WMC/FEM/MT/35. CONFIDENTIAL Dear Sir Walter, I have just returned to London from Geneva, and must apologise for the delay in replying to your letter of the 16th. September regarding various members of the International Brigade. I have written to my Government on this matter, and will let you know as soon as I have their reply. Yours sincerely, P. Azcarate Sir Walter Citrine, K.B.E., Transport House, Smith Square, S.W.1. 292/946/34/130